Comparison of hysterosalpingography and laparoscopy in tubal patency evaluation in infertile women - Ávila Venegas, Carla (2015)
Objectives: To determine correlation of hysterosalpingography and laparoscopy findings in infertile women. Design: Descriptive, retrospective, transversal study. Setting: Instituto Nacional Materno Perinatal, Lima, Peru. Participants: Patients with infertility diagnosis who had both hysterosalpingography and laparoscopy. Interventions: We included 125 infertile patients attended from January 2005 through December 2006. Hysterosalpingographies were ambulatory and findings classified according to Mol et al as without obstruction, obstruction of one tube or bilateral obstruction. Laparoscopy and chromotubation with methylene blue were performed in the follicular phase, under general anesthesia. We considered adhesions, endometriosis, cysts and obstructions as abnormal findings. The laparoscopic intervention most frequently performed was adhesiolysis. We obtained both sensitivity and specificity using contingency table and Wilcoxon ranges non parametric test when comparing hysterosalpingography and laparoscopy findings with infertility type, as well as Spearman correlation test to correlate infertility type and laparoscopic findings. All these tests were supported by SPSS v.10 program. Main outcome measures: Hysterosalpingography sensitivity and specificity. Results: Hysterosalpingography sensitivity was 0,61 and specificity 0,90 when we considered bilateral obstruction as tubal pathology. Conclusions: Hysterosalpingography was a safe method, a good option for initial evaluation of tubal patency in infertility patients. We did not find association between infertility type and laparoscopic findings.